Corporate Social Responsibility: Media Exposure, Kinerja Lingkungan, Kepemilikan Institusional, Leverage, dan Profitabilitas - Muhammad Haykal Adi Pradana; Eny Kusumawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Corporate Social Responsibility is a commitment to improve the welfare of society through prudent business practices and the contribution of company resources. Achieving commercial success in a manner that respects ethical values and respects people, communities, and the natural environment. This study aims to analyze the influence of media exposure, environmental performance, institutional ownership, leverage, and profitability on corporate social responsibility disclosure in the energy and raw materials sector on the Indonesia Stock Exchange (IDX) for the period 2021–2023. The sampling technique used in this study is purposive sampling. A total of 120 companies met the criteria as observation units. The analysis method used was multiple linear regression analysis. The results of the study provide empirical evidence that media exposure and profitability do not affect corporate social responsibility disclosure. Environmental performance, institutional ownership, and leverage affect corporate social responsibility disclosure. The higher the PROPER score, the more extensive the company's CSR disclosure will be. The size of institutional ownership affects CSR disclosure. The higher the leverage ratio, the more extensive the CSR disclosure will be.